Isothermal phase diagram of CaO–SiO2–Nb2O5–La2O3 system at 1300 °C and 1200 °C. Issue 4 (March 2020) - Qiu, Jiyu; Liu, Chengjun; Liu, Zhengyue; Zhu, Deying
Abstract: Thermodynamic properties of CaO–SiO2 –Nb2 O5 –La2 O3 slag system are of great significance for the utilization and application of niobium and rare earth resources. In the present work, the phase equilibria in CaO–SiO2 –Nb2 O5 –La2 O3 system at 1300 °C and 1200 °C have been experimentally investigated. A total of 12 equilibrium phase regions have been determined in the constructed isothermal spatial phase diagram, including five four-phase regions: Liquid + SiO2 +CaNb2 O6 +LaNbO4, Liquid + CaNb2 O6 +Ca2 Nb2 O7 +LaNbO4, Liquid + Ca2 Nb2 O7 +CaO·3SiO2 ·2La2 O3 +LaNbO4, Liquid +10CaO·6SiO2 ·Nb2 O5 +Ca2 Nb2 O7 +LaNbO4, Liquid + LaNbO4 +SiO2 +CaO·3SiO2 ·2La2 O3 ; six three-phase regions: Liquid + SiO2 +LaNbO4, Liquid + CaNb2 O6 +LaNbO4, Liquid + Ca2 Nb2 O7 +LaNbO4, Liquid + CaO·3SiO2 ·2La2 O3 +Ca2 Nb2 O7, L + CaNb2 O6 +Ca2 Nb2 O7, Liquid + SiO2 +CaNb2 O6 ; four two-phase regions: Liquid + SiO2, Liquid + CaNb2 O6, Liquid + LaNbO4, Liquid + Ca2 Nb2 O7 . Subsequently, the isothermal section of CaO–SiO2 –Nb2 O5 -(5%, 10%, 15%, 20%, 25%, 30%) La2 O3 pseudo-ternary systems have been obtained.